2009
DOI: 10.1021/ja905501z
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene-Catalyzed Generation of α,β-Unsaturated Acyl Imidazoliums: Synthesis of Dihydropyranones by their Reaction with Enolates

Abstract: Catalytic generation of alpha,beta-unsaturated acyl imidazolium cations and enolates has been achieved, and their involvement in a Michael addition acylation sequence exploited, to provide a range of dihydropyranones. alpha,beta-Unsaturated enol esters, or alpha,beta-unsaturated acid fluorides in association with TMS enol ethers, serve as appropriate substrates for this reaction. The transformation can also be achieved enantioselectively using catalysts derived from chiral triazolium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
107
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(115 citation statements)
references
References 41 publications
1
107
0
7
Order By: Relevance
“…[8][9][10] Based on these results we decided to use oxidatively generated intermediates C as Michael acceptors to conduct 1,4-addition reactions using soft C nucleophiles. There is precedence in biosynthesis for such processes, and very recently Lupton reported NHC-catalyzed 1,4-addition using activated a,b-unsaturated acid derivatives via intermediates of type C. [11][12][13] Starting with an a,b-unsaturated aldehyde our planned process would comprise two consecutive umpolung reactions at the b position of the a,b-unsaturated aldehyde by a redox-type activation. To liberate the NHC catalyst, the C nucleophile should bear an additional nucleophilic site (Nu 2 ) such that subsequent 1,2-addition to the acylazolium ion D releases the NHC catalyst.…”
Section: Suman De Sarkar and Armido Studer*mentioning
confidence: 99%
“…[8][9][10] Based on these results we decided to use oxidatively generated intermediates C as Michael acceptors to conduct 1,4-addition reactions using soft C nucleophiles. There is precedence in biosynthesis for such processes, and very recently Lupton reported NHC-catalyzed 1,4-addition using activated a,b-unsaturated acid derivatives via intermediates of type C. [11][12][13] Starting with an a,b-unsaturated aldehyde our planned process would comprise two consecutive umpolung reactions at the b position of the a,b-unsaturated aldehyde by a redox-type activation. To liberate the NHC catalyst, the C nucleophile should bear an additional nucleophilic site (Nu 2 ) such that subsequent 1,2-addition to the acylazolium ion D releases the NHC catalyst.…”
Section: Suman De Sarkar and Armido Studer*mentioning
confidence: 99%
“…Interestingly, the generation of 1,3-biselectrophile (II) has been reported from a,b-unsaturated acyl fluorides by Lupton et al, [10] from ynals by Bode et al and Xiao et al [11] and from enals with an oxidant by Studer et al [12] In this communication, we wish to report the generation of a,b-unsaturated acylazolium from bromoenal and the enantioselective reaction with 1,3-dicarbonyl compounds. During the preparation of this manuscript, You et al and Xiao et al reported the enantioselective reaction of a,b-unsaturated acylazolium generated in situ from enals and ynals, respectively.…”
mentioning
confidence: 98%
“…Erste Berichte über Claisen-artige NHC-katalysierte Reaktionen wurden parallel von Lupton et al [26] und Bode et al [27] publiziert. Interessanterweise postulierten beide Gruppen komplett unterschiedliche Mechanismen für solche Transformationen: Lupton et al gingen von einem Mecha- [28] in Gegenwart von Triazol-5-yliden und in der vinylogen Reaktion mit Ketiminen 34 [29] Das dritte Hauptattribut der N-heterocyclischen Carbene ist ihre Basizität.…”
Section: Nhc-katalysierte Transformationenunclassified